1987
DOI: 10.1530/jrf.0.0810567
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body and testis temperatures in the European hedgehog, Erinaceus europaeus, during hibernation and sexual reactivation

Abstract: Simultaneous telemetry of the body and testis temperatures of 8 hedgehogs was carried out during hibernation and during sexual reactivation in spring. Between October and January, when the testes were involuted, the body/testis temperature differential was variable, with mean daily testis temperatures up to 1 degrees C warmer than body temperatures. From mid-February onwards, when plasma testosterone approached maximal concentrations, mean testicular temperatures stabilized 1.4 +/- 0.2 degrees C below body tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Fowler & Racey (1987) reported that the testicular temperature of the ascrotal European hedgehog is also regulated within a narrower range than body temperature although they did not speculate on how this was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Fowler & Racey (1987) reported that the testicular temperature of the ascrotal European hedgehog is also regulated within a narrower range than body temperature although they did not speculate on how this was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse relationships between torpor and spermatogenesis have been explored in rodents and insectivores, and two separate explanations have been developed (e.g. Fowler & Racey, 1987;Darrow et al, 1988;Lee et al, 1990). First, torpor appears to suppress spermatogenesis, probably because of generally low metabolic rates and low body temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most secretory activity must occur during spon¬ taneous arousals, which increase in frequency during the second half of hibernation (Kristoffersson & Soivio, 1964), especially since the pituitary-adrenal axis is known to be blocked during hibernation in the hedgehog (Hoo-Paris, 1971). That neuroendocrine activity during spontaneous arousal plays a part in the termination of hibernation (Wang, 1982) is supported by elevated pro¬ lactin values during winter, the reactivation of the gonads during the second half of hibernation (Fowler & Racey, 1987) and the observations of Saboureau et al (1984) who found that exogenous testosterone in autumn abolished hibernation in hedgehogs.…”
Section: Discussionmentioning
confidence: 92%
“…Plasma testosterone concentrations in male hedgehogs were determined using a heterologous, double-antibody, radioimmunoassay previously described by Fowler & Racey (1987). Minimum distinguishable testosterone levels were 005 ng/ml and intra-and inter-assay coefficients of variation were 10-8% and 13-4% respectively.…”
Section: Hormone Assaysmentioning
confidence: 99%